Serum anti‐Müllerian hormone in subfertile women. (16th September 2015) - Somigliana, Edgardo; Lattuada, Debora; Colciaghi, Barbara; Filippi, Francesca; La Vecchia, Irene; Tirelli, Amedea; Baffero, Giulia M.; Paffoni, Alessio; Persico, Nicola; Bolis, Giorgio; Fedele, Luigi
Abstract: Introduction: The correlation between ovarian reserve and infertility remains unclear. Albeit poorly predictive of pregnancy success in in vitro fertilization cycles, serum anti‐Müllerian hormone (AMH) has been acknowledged as a surrogate measure of ovarian reserve and is commonly evaluated in women seeking pregnancy. Disentangling whether low serum AMH affects natural fecundity is clinically important, as this information helps physicians in providing appropriate counseling to women and may impact on management strategies. Material and methods: This was a nested case‐control study from a prospective cohort of pregnant women undergoing first trimester screening for aneuploidies. Cases were subfertile women having tried to become pregnant for 12–24 months. Controls were subsequent age‐matched fertile women. Inclusion criteria for both cases and controls were: (i) age > 18 years, (ii) natural conception, (iii) regular menstrual cycles (24–35 days). We used quantitative detection of serum AMH and interviews with the women. The main outcome measure was the proportion of women with serum AMH < 1.1 ng/mL. Results: Seventy‐six subfertile women and 76 matched fertile controls were selected. In the two study groups, there were 11 (15%) and 15 (20%) women with serum AMH < 1.1 ng/mL, respectively ( p = 0.52). The crude odds ratio for subfertility in women with low serum AMH was 0.69 [95% confidence interval (CI) 0.29–1.62]. The adjusted odds ratio was 0.85 (95% CI 0.35–2.10). The median (interquartile range) serum concentration of AMH in subfertile and control women was 2.6 (range 1.6–4.0) and 2.8 (range 1.4–4.3) ng/mL, respectively ( p = 0.91). Conclusions: Low serum AMH is not associated with female subfertility.